Legendre Multi-Wavelets Direct Method for Linear Integro-Differential Equations - Abbas, Zulkifly; Vahdati, Saeed; Mohd Atan, Kamel Ariffin; Nik Long, Nik Mohd Asri (Hikari Ltd, 2009)
We use the continuous Legendre multi-wavelets on the interval [0, 1)to solve the linear integro-differential equation. To do so, we reduced the problem into a system of algebraic equations. Illustrative examples are included to demonstrate the validity and applicability of the technique. Comparison has been done with two other methods and it shows that the accuracy of these results are higher than them